Концепція кримінально-правової протидії корупційним злочинам в Україні - Михайленко, Дмитро Григорович; Михайленко, Дмитрий Григорьевич; Mykhailenko, Dmytro H. (My University, 2018)
Дисертація на здобуття наукового ступеня доктора юридичних наук за спеціальністю 12.00.08 - кримінальне право та кримінологія; кримінально-виконавче право. - Національний університет «Одеська юридична академія», Одеса, 2018. У дисертації вперше в Україні здійснено спеціальне комплексне наукове дослідження, в якому на основі поєднання висновків, накопичених у межах різних галузей знань щодо природи корупції та її «імунітету» від антикорупційного законодавства й уявлень щодо актуалізац ії кримінально-правових інструментів протидії їй, вироблено систему наукових положень та обґрунтовано наукові результати в галузі кримінального права і кримінології, які спрямовані на розв’язання проблеми неефективності кримінально-п равової протидії корупц ії в Україні. У дисертації визначено проблеми формування ефективної кримінально-правової політики України у сфері протидії корупції; визначено ресурси теорії «раціонального злочину» в контексті політики протидії корупції в Україні; розкрито поняття та результати диференціації правового регулювання протидії корупції в Україні; визначено соціальну зумовленість диференціації правового регулювання протидії корупції в Україні; виявлені дійсні критерії диференціації правового регулювання протидії корупції; розкрито передумови формування багаторубіжного механізму правової протидії корупції в Україні; встановлено структуру цього механізму; розкрито спеціальні правові норми завершального рубежу правової протидії корупції в контексті класифікації складів злочинів у теорії кримінального права; виявлено функції норми про незаконне збагачення в механізмі кримінально-правової протидії корупції; розкрито норму про незаконне збагачення як інструмент завершального рубежу правової протидії корупції; визначено соціальну зумовленість обмеження принципу презумпції невинуватості нормою про незаконне збагачення в Україні і провести тест на пропорційність щодо такого обмеження; з’ясовано як генезис норми про незаконне збагачення деформував механізм кримінально-правової протидії корупції в У країні; розкрито соціальну зумовленість використання інститутами громадянського суспільства кримінально-правових засобів протидії корупції; надано характеристику кримінально-правовим аспектам приватного кримінального переслідування осіб, які вчинили корупційний злочин. Внесено науково обґрунтовані пропозиції щодо удосконалення КК України в частині кримінально-правової протидії корупційним злочинам.

Диссертация на соискание ученой степени доктора юридических наук по специальности 12.00.08 - уголовное право и криминология; уголовно-исполнительное право. - Национальный университет «Одесская юридическая академия», Одесса, 2018. В диссертации впервые в Украине осуществлено специальное комплексное научное исследование, в котором на основе сочетания выводов, накопленных в рамках различных областей знаний относительно природы коррупции и ее «иммунитета» от антикоррупционного законодательства и представлений по актуализации уголовно-правовых инструментов противодействия ей, выработано систему научных положений и обоснованно научные результаты в области уголовного права и криминологии, направленные на решение проблемы неэффективности уголовно-правового противодействия коррупции в Украине. В диссертации определены проблемы формирования эффективной уголовно-правовой политики Украины в сфере противодействия коррупции; определены ресурсы теории «рационального преступления» в контексте политики противодействия коррупции в Украине; раскрыты понятие и результаты дифференциации правового регулирования противодействия коррупции в Украине; определено социальную обусловленность дифференциации правового регулирования противодействия коррупции в Украине; выявлены истинные критерии дифференциации правового регулирования противодействия коррупции; раскрыто предпосылки формирования многорубежного механизма правового противодействия коррупции в Украине; установлена структура этого механизма; раскрыты специальные правовые нормы завершающего рубежа правового противодействия коррупции в контексте классификации составов преступлений в теории уголовного права; выявлены функции нормы о незаконном обогащении в механизме уголовно-правового противодействия коррупции; раскрыто норму о незаконном обогащении как инструмент завершающего рубежа правового противодействия коррупции; определена социальная обусловленность ограничения принципа презумпции невиновности нормой о незаконном обогащении в Украине и проведен тест на пропорциональность такого ограничения; показано как генезис нормы о незаконном обогащении деформировал механизм уголовно¬правового противодействия коррупции в Украине; раскрыто социальную обусловленность использования институтами гражданского общества уголовно-правовых средств противодействия коррупции; охарактеризованы уголовно-правовые аспекты частного уголовного преследования лиц, совершивших коррупционное преступление. Внесены научно обоснованные предложения по совершенствованию УК Украины в части уголовно-правового противодействия коррупционным преступлениям.

A thesis submitted to the National University «Odesa Law Academy» for a degree of Doctor of Law (Grand PhD) in specialty 12.00.08 «Criminal Law and Criminology; Criminal Enforcement Law» (081 «Law»). - Odesa, 2018. The complex special scientific research of criminal legal counteraction to corruption crimes has been carried out in the thesis. The concept of the mentioned counteraction has been grounded taking into account the current problems of anti¬corruption activity and characteristics of corruption in Ukraine. This scientific research is based on the combination of findings accumulated within different fields of knowledge about the nature of corruption and its «immunity» from anti-corruption legislation and ideas about updating criminal tools countering it. Scientific results which have been obtained are important for science and practice also meet the requirements of scientific novelty. Thus, it has been established that despite the political will to counteract corruption in the echelons of power, higher political leadership in states with a significant spread of corruption is strongly involved into effectively functioning corruption networks of different levels. Therefore, it is objectively unable to formulate and enforce the model of real counteraction to corruption due to several reasons. Firstly, it is constantly influenced by informal rules of conduct that have emerged as a result of the institutionalization of corruption and has its own informal mechanisms of stimulation and pressure. And secondly, it is deeply dependent on other members of the corrupt pyramid (network) that carry out a significant, often informal, influence on the state political structures. It lias been substantiated that in the context of counteraction to corruption in Ukraine there is a differentiation of legal regulation of such a counteraction as a single phenomenon and at the same time as a way of organizing the nonnative field. As a result of such differentiation there are legal regimes for counteraction to corruption, which have features depending on its sphere. It has been established that within the legal framework of the Ukrainian anticorruption mechanism (the mechanism of legal counteraction to corruption in Ukraine) the following general legal regimes could be distinguished: 1) the legal regime for counteraction to corruption in the sphere of public administration, within which a special legal regime is established to combat corruption in higher levels of government; 2) the legal regime for combating corruption in the sector of public services; 3) the legal regime for combating corruption in the private sector; 4) the legal regime for corruption counteraction in the sphere of non-government activities; 5) the legal regime for combating corruption in the field of sports (official sports competitions). It lias been determined that the frontiers of anticorruption law are groups of rules of law, which are used alternately to counteract corruption and differ in purpose to influence the relevant legal relationship and taking into account the stage of the development of illegal activity (the emergence of risks, the commission of a socially dangerous act, the realization of assets, obtained as a result of this act) when the rules of a particular frontiers are to be applied. It has been determined that in Ukraine, the multilateral mechanism of legal counteraction to corruption has a trilateral structure, where each of the frontiers has the appropriate elements (norms of law). The legal norms of the preliminary anti¬corruption frontier are a set of anti-corruption legal norms that, in order to prevent corruption, to eliminate corruption risk and (or) to prevent corruption, establish the following: 1 ) preventive anti-corruption mechanisms, and 2) the grounds for liability for behavior that is not yet a corruption crime but forms a certain corruption risk, the presence of which is already socially dangerous (corruptive crimes, delinquencies that create a corruption threat) or whose development makes the commission of corrupt crimes potential. The legal norms of the main frontier of combating corruption are a set of anti-corruption legal norms that establish the grounds for liability for acts that are corrupt crimes. The legal norms of the final frontier of counteraction to corruption are a set of anti-corruption legal norms, which establish the grounds for responsibility for behavior, or past acts of corruption (corruptive crimes of the main frontier) remaining latent. The effective structure of the crime, which is such a crime, where the actus reus needs to establish only the results of a criminal act (socially dangerous consequences, products of criminal activity or other indicators of an act committed before, etc.). Taking into account the basis of a rebuttable presumption, it is possible to declare the commission of a socially dangerous an act that led to the indicated results. On the basis of the study of the genesis of the norm on illegal enrichment (Article 368-2 of the Criminal Code), it has been established that constant changes of even one norm of the Criminal Law may be a factor of the deformation of the mechanism of criminal legal counteraction to all groups of criminal encroaclunents (in the case of a norm on illicit enrichment - corruption crimes). The methodology of the proportionality test for the norm of illegal enrichment has been applied in the research paper. The idea of adoption of private prosecution in the legal system of Ukraine as an effective instrument of criminal legal opposition to institutionalized corruption at higher levels of power has been improved. The criminal law elements of the mentioned institute have been substantiated.
дис. ... доктора юрид. наук: 12.00.08
Михайленко Д.Г. Концепція кримінально-правової протидії корупційним злочинам в Україні: дис. ... доктора юрид. наук: 12.00.08 / Михайленко Дмитро Григорович. - Одеса, 2018. - 505 с.
Keywords: корупція; інституціоналізована корупція; політична воля; протидія корупції; теорія «раціонального злочину»; корупційні злочини; диференціація правового регулювання протидії корупції; багаторубіжний механізм правової протидії корупції; незаконне збагачення; принцип презумпції невинуватості; тест на пропорційність; фінансови й контроль; приватне кримінальне переслідування; коррупция; институционализированая коррупция; политическая воля; противодействие коррупции; теория «рационального преступления»; коррупционные преступления; дифференциация правового регулирования противодействия коррупции; многорубежный механизм правового противодействия коррупции; незаконное обогащение; принцип презумпции невиновности; тест на пропорциональность; финансовый контроль; частное уголовное преследование; corruption; institutionalized corruption; political will; counteraction to corruption; Rational Crime Theory; corruption crime; differentiation of legal regulation of counteraction to corruption; multilateral mechanism of legal counteraction to corruption; illegal enrichment; presumption of innocence principle; proportionality test; financial control; private prosecution